Validation study of the Alzheimer's Disease Assessment Scale‐Cognitive Subscale for people with mild cognitive impairment and Alzheimer's disease in Chinese communities. (1st August 2019) - Yang, Hongyu; Cheng, Zaohuo; Li, Zemei; Jiang, Yan; Zhao, Jinfa; Wu, Yue; Gu, Shouquan; Xu, Hong
Abstract : Objective: Our study aimed to verify the validity of the Chinese version of Alzheimer's Disease Assessment Scale‐Cognitive Subscale (ADAS‐Cog) for the community‐dwelling older people in China. Methods: A total of 1276 individuals composed by 628 normal controls (NCs), 572 people living with mild cognitive impairment (MCI), and 76 people living with Alzheimer's disease (AD) were recruited for the current study. All of the participants underwent ADAS‐Cog, clinical interview and examination, Quick Cognitive Screening Scale for the Elderly, and Activities of Daily Living Scale. The sensitivity and specificity of ADAS‐Cog were calculated, and a receiver operating characteristic curve (ROC curve) was drawn to decide the optimal cutoff points of ADAS‐Cog for screening MCI and AD. Results: Statistically significant differences were observed among the three groups ( P <. 001, NC < MCI <AD), in terms of the total and subtask scores of ADAS‐Cog. The optimal cutoff value for MCI was 10 points with an area under the curve (AUC) of 0.824, sensitivity of 61.4%, and specificity of 93.2%. Comparatively, the best cutoff value for AD was 15 points with an AUC of 0.905, sensitivity of 73.7%, and specificity of 92.4%. The overall accuracy was 70.5%, and the accuracy of diagnosing cognitively healthy older people, MCI patients, and AD patients was 81.7%, 58.0%, and 71.1%, respectively. Conclusion: The present study illustrates that the Chinese version of the ADAS‐Cog total score is able to detect cognitive impairment of AD patients in Chinese communities but has a lower efficacy for MCI.